2022
DOI: 10.1002/jmv.27872
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of an inactivated SARS‐CoV‐2 vaccine in people living with HIV: A cross‐sectional study

Abstract: We aimed to analyze the efficacy and safety of an inactivated SARS-CoV-2 vaccine in people living with HIV (PLWH). A total of 143 PLWH and 50 healthy individuals were included in this study. A commercially available magnetic chemiluminescence enzyme immunoassay kit was used to detect serum IgG and IgM antibodies against SARS-CoV-2. Serum levels of SARS-CoV-2-specific IgG were significantly higher in the control group than in the PLWH group (p = 0.001). Overall, 76% of individuals in the control group were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…[ 110 •] BBIBP-CorV (2 doses) Open-label two-arm non-randomized study (China) 42 PLWH: 29 males, 13 females; mean age: 42.7 years 28 HIV-negative controls: 16 males, 12 females; mean age: 37.8 years Mean CD4 + T-cell count: 659/µL (SD: 222) All PLWH on cART Plasma HIV-RNA: - > 20 copies/mL: n = 12 - < 20 copies/mL: n = 8 - undetectable: n = 22 Participants with prior SARS-CoV-2 infection excluded Anti-RBD Ig (ELISA) Neutralizing antibody activity (chemiluminescent reaction; spike-ACE2 binding inhibition assay) SARS-CoV-2–specific T-cells (ICS by flow cytometry after stimulation of PBMCs with spike peptide pool) Time-points: baseline; 4 weeks after first dose; 4 weeks after second dose Similar anti-RBD Ig, neutralization activity and T-cell responses between PLWH and HIV-negative controls Lower humoral responses in PLWH with low CD4/CD8 ratio compared to PLWH with medium or high ratio Cai, et al . [ 132 ] BBIBP-CorV or CoronaVac (2 doses) Single-centre cross-sectional study (China) 143 PLWH: 140 (97.9%) males, 3 (2.1%) females; mean age 32.55 years (SD: 8.69) 50 HIV-negative controls: 48 (96%) males, 2 (4%) females; mean age: 29.84 (SD: 8.51) Mean CD4 + T-cell count: 398.96/µL (SD: 202.31) 116 (81.1%) PLWH on cART Individuals with prior SARS-CoV-2 infection included Anti-RDB IgG, anti-N IgM (magnetic chemiluminescence enzyme assay) Neutralizing antibody activity (live virus neutralization assay) Time-points: 64.46 ± 41.22 or 35.78 ± 27.99 days after vaccination in HIV-negative controls and PLWH, respectively Anti-RBD IgG levels lower in PLWH than HIV-negative controls Positive correlation between anti-RBD IgG and CD4 + T-cell counts Anti-N IgM levels and neutralization ability against WT and Delta variant similar between groups Zeng, et al . [ 112 ] BBIBP-CorV or CoronaVac (2 doses) Longitudinal study (China) 132 PLWH: 119 (90.2%) males, 13 (9.8%) females; mean age: 34.05 years (SD: 8.37) 130 HIV-negative controls: 115 (88.5%) males, 15 (11.5%) females; mean age: 34.4 years (SD: 8.9) CD4 + T-cell count strata: - 200–349/µL: 14.4% - 350–499/µL: 26.5% - ≥ 500/µL: 49.2% cART: 87.9% of PLWH under stable treatment for more than 6 months; 7.6% less than 6 months; 4.5% without treatment Plasma HIV-RNA < 50 copies/mL: 90.9% Participants with prior SARS-CoV-2 infection excluded Anti-RB...…”
Section: Immune Responses To Sars-cov-2 Vaccines In Plwhmentioning
confidence: 99%
“…[ 110 •] BBIBP-CorV (2 doses) Open-label two-arm non-randomized study (China) 42 PLWH: 29 males, 13 females; mean age: 42.7 years 28 HIV-negative controls: 16 males, 12 females; mean age: 37.8 years Mean CD4 + T-cell count: 659/µL (SD: 222) All PLWH on cART Plasma HIV-RNA: - > 20 copies/mL: n = 12 - < 20 copies/mL: n = 8 - undetectable: n = 22 Participants with prior SARS-CoV-2 infection excluded Anti-RBD Ig (ELISA) Neutralizing antibody activity (chemiluminescent reaction; spike-ACE2 binding inhibition assay) SARS-CoV-2–specific T-cells (ICS by flow cytometry after stimulation of PBMCs with spike peptide pool) Time-points: baseline; 4 weeks after first dose; 4 weeks after second dose Similar anti-RBD Ig, neutralization activity and T-cell responses between PLWH and HIV-negative controls Lower humoral responses in PLWH with low CD4/CD8 ratio compared to PLWH with medium or high ratio Cai, et al . [ 132 ] BBIBP-CorV or CoronaVac (2 doses) Single-centre cross-sectional study (China) 143 PLWH: 140 (97.9%) males, 3 (2.1%) females; mean age 32.55 years (SD: 8.69) 50 HIV-negative controls: 48 (96%) males, 2 (4%) females; mean age: 29.84 (SD: 8.51) Mean CD4 + T-cell count: 398.96/µL (SD: 202.31) 116 (81.1%) PLWH on cART Individuals with prior SARS-CoV-2 infection included Anti-RDB IgG, anti-N IgM (magnetic chemiluminescence enzyme assay) Neutralizing antibody activity (live virus neutralization assay) Time-points: 64.46 ± 41.22 or 35.78 ± 27.99 days after vaccination in HIV-negative controls and PLWH, respectively Anti-RBD IgG levels lower in PLWH than HIV-negative controls Positive correlation between anti-RBD IgG and CD4 + T-cell counts Anti-N IgM levels and neutralization ability against WT and Delta variant similar between groups Zeng, et al . [ 112 ] BBIBP-CorV or CoronaVac (2 doses) Longitudinal study (China) 132 PLWH: 119 (90.2%) males, 13 (9.8%) females; mean age: 34.05 years (SD: 8.37) 130 HIV-negative controls: 115 (88.5%) males, 15 (11.5%) females; mean age: 34.4 years (SD: 8.9) CD4 + T-cell count strata: - 200–349/µL: 14.4% - 350–499/µL: 26.5% - ≥ 500/µL: 49.2% cART: 87.9% of PLWH under stable treatment for more than 6 months; 7.6% less than 6 months; 4.5% without treatment Plasma HIV-RNA < 50 copies/mL: 90.9% Participants with prior SARS-CoV-2 infection excluded Anti-RB...…”
Section: Immune Responses To Sars-cov-2 Vaccines In Plwhmentioning
confidence: 99%
“…In one month after the 3rd vaccination, our results showed that the NAb seroconversion in cohort 2 was 93.9% (93/99) ( Table 6 ), which is close to the rate of PLWH vaccinated with inactivated COVID-19 vaccines (Sinopharm Inactivated Whole Virus or SinoVac Inactivated Whole Virus) in Guangzhou (97%). 23 Moreover, the gradual reductions in the NAb level and seroconversion rate of NAb were noted over time. 24 Broadly speaking, the 3rd dose of inactivated COVID-19 vaccine effectively induced SARS-CoV-2-specific NAb seroconversion (over 60%) in two PLWH cohorts.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that PLWH on ART mount detectable cellular and humoral responses after SARS-CoV-2 infection [ 5 ]. This is also the case for SARS-CoV-2 vaccination [ 6 , 10 , 13 ], although most of these studies have only assessed IFNγ production after one or two SARS-CoV-2 vaccine doses. However, in our study, we analyzed intracellular levels and production patterns of three different cytokines in CD4 and CD8 T-cells, excluding innate immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, incomplete CD4 T-cell restoration and low CD4:CD8 ratios may impede the development of anti-SARS-CoV-2 immune responses following vaccination and infection, especially before booster vaccination [ 5 , 6 , 8 ]. Although we have recently shown that SARS-CoV-2 vaccine-induced humoral responses in PLWH on ART are not significantly different from HIV seronegative individuals [ 9 ], fewer studies have compared vaccine-induced SARS-CoV-2-specific T-cell immunity between PLWH and HIV seronegative individuals [ 6 , 10 , 11 ], of which only one has assessed responses after the 3rd dose [ 11 ]. Herein, we longitudinally assessed SARS-CoV-2-specific T-cell responses and changes in T-cell subset distributions in PLWH and HIV seronegative persons without prior SARS-CoV-2 infection, up to one month following the third SARS-CoV-2 vaccine dose.…”
Section: Introductionmentioning
confidence: 99%